Pengaruh Tummy Time Exercise Terhadap Kemampuan Motorik Kasar Bayi Usia 12 - 24 Minggu - Kahfi, Muhammad (2005)
ABSTRACT STUDY PROGRAM OF PHYSIOTHERAPY UNDERGRADUATE HEALTH FACULTY MUHAMMADIYAH UNIVERSITY OF SURAKARTA MINITHESIS, September 29th 2015 MUHAMMAD KAHFI/ J120110014 "THE EFFECT OF TUMMY TIME EXERCISE ON THE GROSS MOTOR SKILLS OF INFANTS AGE 12 - 24 WEEKS" (Counseled by: Agus Widodo S.Fis., M.Fis and Dwi Kurniawati SST. FT., M.Kes) Background: Each baby has grown gross motor skills are different even though they follow the same general pattern. To optimize the development of gross motor needed stimulation. Tummy time exercise is a one of stimulating which will hold the baby weight with the help of the chest and abdomen muscles to train the baby to lift his head and other body control. The Objective of Research: To know the effect of Tummy time exercise on the gross motor skills of infants aged 12-24 weeks. The Benefit of Research: It could know the effect of Tummy time exercise on the gross motor skills of infants aged 12-24 weeks. The Method of Research: This type of research in this study was Quasi Experimental research design with pre and post test with control group design. The sampling technique is simple random sampling with insklusi and exclusion criteria. Measuring instruments used to measure gross motor skills is the Gross Motor Function Measure (GMFM). The data analysis using descriptive analysis. Result of the Research: The descriptive analysis obtained gross motor development treatment group increased significantly when compared to the control group gross motor development. Conclusion: There is influence of tummy time exercise on the gross motor skills of infants aged 12-24 weeks. Keywords: Tummy Time, Gross Motor.